Rehabilitation, Using Guided Cerebral Plasticity, of a Brachial Plexus Injury Treated with Intercostal and Phrenic Nerve Transfers - Dahlin, Lars B. (Front Neurol, 2017)
Recovery after surgical reconstruction of a brachial plexus injury using nerve grafting and nerve transfer procedures is a function of peripheral nerve regeneration and cerebral reorganization. A 15-year-old boy, with traumatic avulsion of nerve roots C5–C7 and a non-rupture of C8–T1, was operated 3 weeks after the injury with nerve transfers: (a) terminal part of the accessory nerve to the suprascapular nerve, (b) the second and third intercostal nerves to the axillary nerve, and (c) the fourth to sixth intercostal nerves to the musculocutaneous nerve. A second operation—free contralateral gracilis muscle transfer directly innervated by the phrenic nerve—was done after 2 years due to insufficient recovery of the biceps muscle function. One year later, electromyography showed activation of the biceps muscle essentially with coughing through the intercostal nerves, and of the transferred gracilis muscle by deep breathing through the phrenic nerve. Voluntary flexion of the elbow elicited clear activity in the biceps/gracilis muscles with decreasing activity in intercostal muscles distal to the transferred intercostal nerves (i.e., corresponding to eighth intercostal), indicating cerebral plasticity, where neural control of elbow flexion is gradually separated from control of breathing. To restore voluntary elbow function after nerve transfers, the rehabilitation of patients operated with intercostal nerve transfers should concentrate on transferring coughing function, while patients with phrenic nerve transfers should focus on transferring deep breathing function.